Vegetable intake in Australian children and adolescents: the importance of consumption frequency, eating occasion and its association with dietary and sociodemographic factors. Issue 3 (25th September 2019) - Fayet-Moore, Flavia; McConnell, Andrew; Cassettari, Tim; Tuck, Kate; Petocz, Peter; Kim, Jean
Abstract: Objective: We aimed to profile vegetable consumption and its association with dietary and sociodemographic factors. Design: Secondary analysis of a nationally representative nutrition survey. 'Vegetables' refers to non-discretionary 'vegetables and legumes/beans' as defined by the Australian Dietary Guidelines (ADG). Prevalence of vegetable consumption, frequency of intake, proportion meeting ADG recommendations, most popular food groups, intake at each reported eating occasion, and the profile of high and low vegetable consumers (based on the median servings) were determined. Setting: Australian 2011–2012 National Nutrition and Physical Activity Survey. Participants: Children and adolescents aged 2 to 18 years ( n 2812). Results: Vegetables were consumed by 83·0% (95% CI 81·6, 84·4%) of participants, but the median vegetable servings was less than a third of the ADG recommendations. 'Leaf and stalk vegetables' and 'potatoes' were the most popular vegetable-dense food groups at lunch and dinner, respectively. Sixty-four percent had vegetables once a day, and predominantly at dinner. Vegetable frequency was positively associated with daily vegetable servings and variety. Participants who consumed vegetables twice a day generally had vegetables at both lunch and dinner and had nearly double the servings (2·6, sd 1·9) of those who consumed them once (1·5, sd 1·5). High vegetable consumers were older, had higher total energy, but lower discretionary energy intake and were less likely to be at risk of metabolic complications. Conclusion: Increasing the frequency of vegetable consumption may assist with increasing daily vegetable servings. A focus on consuming vegetables at lunch may assist with increasing both total servings and variety.